A database of handwriting samples for applications in forensic statistics - Crawford, Amy (Data Brief, 2019)
Handwriting samples were collected from 90 adults for the purpose of developing statistical approaches to the evaluation of handwriting as forensic evidence. Each participant completed three data collection sessions, each at least three weeks apart. At each session, a survey was completed and three writing prompts were each transcribed three times. In total, the repository includes 2430 handwriting sample images as well as demographic and session specific information for all 90 participants. The writing samples were scanned and instructional header text was cropped out to obtain the raw writing data as image files. Survey data are provided in table format. Reliable methods for data management were incorporated through systematic document generation, QR code text embedding, and the development of an application to facilitate data entry and automated file naming and handling. The data presented in this article were collected by researchers at the Center for Statistics and Applications in Forensic Evidence (CSAFE) at Iowa State University.